Numerical study of hydrogen dispersion in a fuel cell vehicle under the effect of ambient wind. (23rd August 2019) - Yu, Xing; Wang, Changjian; He, Qize
Abstract: In the rescue of hydrogen-fueled vehicle accidents, once accidental leakage occurs and hydrogen enters the cabin, the relatively closed environment of the vehicle is prone to hydrogen accumulation. Excessive hydrogen concentration inside the vehicle cabin may cause suffocation death of injured passengers and rescue crews, or explosion risk. Based on hydrogen fuel cell vehicle (HFCV) with hydrogen storage pressure 70 MPa, four different scenarios (i. with opened sunroof, ii. opened door windows, iii. opened sunroof and door windows and iv. opened sunroof, door windows and rear windshield) under the condition of accidental leakage were simulated using computational fluid dynamics (CFD) tools. The hydrogen concentration inside the vehicle and the distribution of flammable area (>4% hydrogen mole fraction) were analyzed, considering the effect of ambient wind. The results show that in the case of convection between interior and exterior of the vehicle via the sunroof, door windows or rear windshield, the distribution of hydrogen inside the vehicle is strongly affected by the ambient wind speed. In the least risk case, ambient wind can reduce the hydrogen mole fraction in the front of the vehicle to less than 4%, however the rear of the vehicle is always within flammable risk. Highlights: Hydrogen dispersion in a HFCV was simulated under various wind speeds. Hydrogen concentration inside the vehicle is strongly affected by wind speed. The Ambient wind may protect the front of vehicle away from flammability.